NAHDLATUL ULAMA AND THE PRODUCTION OF MUSLIM INTELLECTUALS IN THE BEGINNING OF 21ST CENTURY INDONESIA (State Islamic University (UIN) of Sunan Ampel Surabaya, 2017)
Social transformation carried out by the New Order government through the development program resulted on the emergence of various face of Muslim intellectuals in Indonesia. They are divergent and located in a great variety of institutional settings as well as in the interstices between a number of institutional orders. This paper aims at analysing the production and dynamics of Muslims intellectuals within the largest Muslim mass organisations in Indonesia, Nahdlatul Ulama (NU/The Awakening of Muslim Scholars). It begins with the discussion of scholarly perspectives of the correlation between Islamic organisation and Muslim intellectuals. It then examines the production of Muslim intellectuals within NU, questioning the issue of young and old generation, and finally analysing the relationship between institution and the development of intellectualism within NU.